Effective monetary policy conservatism: A comparison of 11 OECD countries - Michael Berlemann; Kai Hilscher (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
Modern monetary economists argue that institutional aspects such as central bank independence and central bank conservatism play an important role for the performance of an economy. In order to be able to compare the effects of different institutions it is necessary to measure both central bank independence and conservatism. In this paper we propose a new methodology of uncovering the degree of effective monetary policy conservatism from observed central bank behavior. Employing a variant of the Barro-Gordon-model we derive an optimal prime rate reaction function and show that more effectively conservative monetary policy tends to react less active to shocks to the real economy. In order to illustrate the proposed methodology we then estimate a common prime rate reaction function for a sample of 11 central banks in a panel setting and allow the reaction to real disturbances to differ between countries.
Keywords: F21; F23; O55; 330